Polygenic Variation and Character Association in Panicle Characters of some Recombinant Inbred Iines (RIL’s) of Basmati Derivative in Sunderbans Area of West Bengal - SENAPATI, B.K.; KUMAR, AWANEET (Journal of the Indian Society of Coastal Agricultural Research, 2023)
Fourteen recombinant inbred lines (RIL’s) of progenies obtained from IR 30/Basmati 370 cross derivative were evaluated along with two popular varieties viz. Khitish (IET4094) and Minikit (IET 4786) for 16 biometrical characters during November 2011- March 2012 at Regional Research Station, Coastal Saline Zone, Bidhan Chandra Krishi Vishwavidyalaya, Kakdwip, South 24 Parganas, West Bengal, India. Except number of primary branches per panicle, fertility percentage, grain breadth, grain L/B ratio and kernel breadth all the characters studied showed significant differences among the genotypes. Six lines (S14, S10, S1, S2, S3 and S4) possessed significantly higher grain yield than superior check variety. High estimates of PCV and GCV were recorded for number of grains per panicle, florets number per panicle, number of panicle per plant, kernel length, kernel L/B ratio and panicle weight. High heritability was observed for 1000 grain weight, grain yield per plant, floret number per panicle, panicle length, number of panicle per plant, kernel length and kernel L/B ratio. High genetic advance was observed for florets number per panicle, number of grains per panicle, fertility % and number of panicle per plant. Genetic advance as percentage of mean was highest for floret number per panicle and it was lowest for grain breadth. High heritability coupled with high GA was recorded for floret number per panicle and number of grains per panicle. It indicated the predominance of additive gene action for controlling these characters. Therefore, these characters can be improved simply through selection. High heritability associated with low genetic advance was observed for panicle length, number of panicle per plant, 1000 grain weight, kernel length and kernel L/B ratio. It suggested non-additive gene action for the expressions of these characters. The magnitude of genotypic correlation coefficient was in general higher than that of the corresponding phenotypic ones.